Análisis para la automatización del proceso de matrículas y promociones de los estudiantes de la Unidad Educativa Abdón Calderón Muñoz de la Parroquia Barreiro nuevo del cantón Babahoyo. - Quiroz Villacis, Carmen Marlene (2023)
This work for the end of the degree comprises the case study of the Analysis of the automation for the Process of Certificates of Enrollment and Promotions of the Educational Unit Abdón Calderón Muñoz, The main purpose of the proposal allows to establish the theoretical, conceptual and referential framework. The objective for the analysis of this research and its respective rules and guidelines of the functionality is to reduce the time spent in manual processes as well as in the certificates of enrollment, promotions and qualifications and to optimize the time spent in each one. For this reason, this process analysis will allow the institution as well as the administrative staff, teachers and parents to obtain information more agile and efficient.